2020
DOI: 10.1016/s2542-5196(20)30222-9
|View full text |Cite
|
Sign up to set email alerts
|

Projections of excess mortality related to diurnal temperature range under climate change scenarios: a multi-country modelling study

Abstract: Summary Background Various retrospective studies have reported on the increase of mortality risk due to higher diurnal temperature range (DTR). This study projects the effect of DTR on future mortality across 445 communities in 20 countries and regions. Methods DTR-related mortality risk was estimated on the basis of the historical daily time-series of mortality and weather factors from Jan 1, 1985, to Dec 31, 2015, with data for 445 communities across 20 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(42 citation statements)
references
References 30 publications
(70 reference statements)
0
41
0
1
Order By: Relevance
“…We used Monte Carlo simulations to calculate the confidence intervals of the estimates, using 1,000 replicates. 30,31…”
Section: Excess Emergency Room Visit Attributable To Air Pollutionmentioning
confidence: 99%
See 1 more Smart Citation
“…We used Monte Carlo simulations to calculate the confidence intervals of the estimates, using 1,000 replicates. 30,31…”
Section: Excess Emergency Room Visit Attributable To Air Pollutionmentioning
confidence: 99%
“…Risk estimates for air pollution were translated into the excess ER visits attributable to air pollution, to demonstrate the change in ER burden due to air pollution exposure, 29 following a method used in previous studies. 30,31 For each pollutant, we calculated the daily excess ER visits attributable to air pollution in each region using the corresponding RR (calculated from the BLUP) associated with the level of air pollution of each day. The sum of attributable ER visits represents the total excess number of ER visits attributable to air pollution, and its ratio with the total number of ER visits provides the total excess fraction of such visits attributable to air pollution.…”
Section: Excess Emergency Room Visit Attributable To Air Pollutionmentioning
confidence: 99%
“…A recent research showed Eastern Europe had the highest heatrelated excess death rate [35]. Time-series analyses results proved that higher diurnal temperature range was associated with excess mortality [36]. Fouillet et al conducted an analysis of the August 2003 heat wave in France.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies examined the relation between heat and, respectively, respiratory and cerebrovascular mortality. However, these researches yielded conflicting results [10,[33][34][35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…The stochastic intervention framework for time series data introduced in this paper is the first approach which allows for identifications and estimation of causal quantities defined by stochastic interventions on multiple time series. We believe this statistical framework addresses one of the emerging methodological needs in climate change and environmental health research where researchers often collect time series data from multiple geographic locations seeking causal evidence among representative regions (Liu et al 2019, Lee et al 2020. We expect the proposed framework can be adapted without methodological barriers to science and policy-relevant research in political science, economics, and law where considerable amount of spatial-temporal data are generated and collected.…”
Section: Discussionmentioning
confidence: 99%